PENINGKATAN KETERAMPILAN MENULIS TEKS NARASI MENGGUNAKAN TEKNIK MIND MAPPING BERBANTUAN MEDIA FLASHCARD DI KELAS III SDN 15 ULU GADUT KOTA PADANG (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study was conducted due to the low level of narrative writing skills among third-grade students at SDN 15 Ulu Gadut, Padang. Students experienced difficulties in generating ideas, organizing story structures coherently, and applying correct spelling and punctuation based on EYD Edition V. In addition, previous teaching practices lacked structured guidance to support students in planning their writing. This research aimed to examine the improvement of narrative writing skills through the use of mind mapping techniques supported by flashcard media. The study employed a Classroom Action Research (CAR) design involving 18 students conducted in two cycles. The results showed that mind mapping helped students systematically organize their ideas according to narrative structure (beginning, middle, and ending), while flashcards functioned as visual stimuli to enhance imagination and vocabulary. The integration of both strategies effectively improved students’ ability to produce coherent, well-structured, and grammatically appropriate narrative texts.